Food packaging design with different elements of the country of origin identification - Jarossová, Malgorzata A.; Gondárová, Jana; Gordanová, Jana (Opakowania produktów spożywczych z różnymi elementami identyfikującymi kraj pochodzenia produktu, 2019)
The study aimed to assess the possibility of identifying the country of origin of a product by placing various cultural elements of a given country on their packaging. A quantitative research method was used to obtain primary data. 193 respondents from Slovakia took part in the study (71.5% women and 28.5% men). In the article, we describe the responses of respondents to 5 questions concerning: cultural elements on food packaging identifying the country of origin, respondents buying food products in packaging with cultural elements, reasons for not buying them, paying attention to the presence of cultural elements on some food packaging and the degree to which this packaging reminds respondents of Slovakia. The conducted research confirmed the authors’ assumptions that approximately 80% of all respondents would be willing to buy a product with a cultural motif on the product packaging (the percentage of men preferring these motifs was smaller than women, i.e. 72% compared to 80%)
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2019, Nr 4 (35), s. 28-41
Keywords: design; food packaging; country of origin; product; projekt; opakowanie żywności; kraj pochodzenia; produkt